2007
DOI: 10.1111/j.1461-9563.2007.00350.x
|View full text |Cite
|
Sign up to set email alerts
|

A historical review of research on the weaver ant Oecophylla in biological control

Abstract: 1 Although the weaver ant Oecophylla is the first written record of biological control, dating from 304 ad , there have been fewer than 70 scientific publications on this predator as a biological control agent in Asia, from the early 1970s onwards, and fewer than 25 in Africa. 2 Apart from crop-specific ecological and perceptual factors, a historical review shows that political and market forces have also determined the extent to which Oecophylla was incorporated into research and development programmes. 3 In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
111
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(114 citation statements)
references
References 65 publications
(73 reference statements)
2
111
0
1
Order By: Relevance
“…Studies (Sinzogan et al, 2008;Van Mele, 2008a) involving citrus farmers elsewhere found that farmers generally perceived that the presence of O. longinoda in orchards improved fruit quality. However, most respondents in the present study did not observe any difference between the quality of fruits harvested from trees with and without O. longinoda.…”
Section: Discussionmentioning
confidence: 99%
“…Studies (Sinzogan et al, 2008;Van Mele, 2008a) involving citrus farmers elsewhere found that farmers generally perceived that the presence of O. longinoda in orchards improved fruit quality. However, most respondents in the present study did not observe any difference between the quality of fruits harvested from trees with and without O. longinoda.…”
Section: Discussionmentioning
confidence: 99%
“…Many ants (Hymenoptera, Formicidae) are generalist predators and have the potential to control herbivore abundance, reducing the plant damage while increasing plant growth,  Corresponding author Email: rksdias@kln.ac.lk reproduction and yield (Majer 1972, Leston 1973, Schmitz et al 2000, Symondson et al 2002, Van Mele 2008 in agro-ecosystems (Way & Khoo 1992, Peng & Christian 2004, 2005, Peng et al 1995, 1997, 1999, 2014. Cashew, Anacardium occidentale L., a tree crop native to coastal Brazil, grown in many other countries including Sri Lanka (Cashew Corporation of Sri Lanka 2010) has high economic value as a fruit, nut and oil globally (Blomhoff et al 2006, FAO 2013.…”
Section: Introductionmentioning
confidence: 99%
“…As biocontrol agents weaver ants have proven efficient in controlling several pests in plantations of mango (Peng & Christian, 2004;Peng & Christian, 2005a;Peng & Christian, 2005b ;Peng & Christian, 2006;Peng & Christian, 2007;Davidson et al, 2007;Adandonon et al, 2009;Van Mele et al, 2007), citrus (Huang & Yang, 1987;Van Mele & Cuc, 2000;Van Mele et al, 2002;Van Mele, 2008), cashew (Peng et al, 1995;Peng et al, 1997;Dwomoh et al, 2009, Olotu et al, 2013, coconut (Way, 1954;Vanderplank, 1960;Varela, 1992;Sporleder & Rapp, 1998) and cocoa (Ayenor et al, 2004;Ayenor et al, 2007). For reviews see Way and Khoo (1992) and Offenberg (2015).…”
mentioning
confidence: 99%